Activation of AMPK inhibits pulmonary arterial smooth muscle cells proliferation. (1st June 2014) - Wu, Yuanyuan; Liu, Lu; Zhang, Yonghong; Wang, Guizuo; Han, Dong; Ke, Rui; Li, Shaojun; Feng, Wei; Li, Manxiang
ABSTRACT: The aims of the present study were to examine the effect of AMPK activation on pulmonary arterial smooth muscle cells (PASMCs) proliferation and to address its potential mechanisms. ET-1 dose and time-dependently induced PASMCs proliferation, and this effect was suppressed by a selective AMPK activator metformin. The results of the study further indicated that the proliferation of PASMCs stimulated by ET-1 was associated with the increase of Skp2 and decrease of p27, and metformin reversed ET-1-induced Skp2 elevation and raised p27 protein level. Our study suggests that activation of AMPK suppresses PASMCs proliferation and has potential value in negatively modulating pulmonary vascular remodeling and therefore could prevent or treat the development of pulmonary arterial hypertension (PAH).